A change of paradigm in Afghanistan: Afghan government ownership instead of donor priorities - Citha Doris Maaß (Stiftung Wissenschaft und Politik (SWP), 2008)
At the Afghanistan conference taking place in Paris in mid-June some delegates facing forthcoming elections at home may use the occasion to counter widespread voters' criticism of international operations in Afghanistan. President Karzai, who is also involved in the preliminary phase of an election campaign, will call for a change of paradigm in order to rid himself of his reputation as a 'puppet of the donor countries'. Citing two new strategy papers for the period up to 2013, he has advocated 'government ownership'. It seems logical, given the increased confidence of leading Afghan elites on the one hand and the task of adjusting international stabilisation targets on the other, for political responsibility to be gradually handed over to the Afghan government by 2013. The time remaining until the final handover should be used intensively to build up the capacity of Afghan partners, above all the army
Keywords: 320